Menakar Kelayakan Pinjaman Pemulihan Ekonomi Nasional (PEN) Daerah pada Kabupaten Bone Bolango - William Indra S. Mooduto; Abdul Wahab Podungge; Muliyani Mahmud (Jambura Accounting Review, 2021)
This study aims to assess the feasibility of regional national economic recovery loans (PEN) in Bone Bolango Regency, by analyzing 4 (four) indicators of eligibility requirements for granting Regional PEN Loans, namely (1) the area is affected by Covid 19; (2) have a Regional Economic Recovery program or activity that supports the National Economic Recovery program; (3) The remaining amount of the loan plus the amount of the loan to be withdrawn does not exceed 75 percent of the general revenue of the previous year's Regional Government Budget; (4) meet the ratio of regional financial capacity to repay regional loans of at least 2.5 percent.The first and second indicators were tested using desk study analysis. then the third and fourth indicators are tested by analyzing the financial statements of the Bone Bolango Regency in 2020 and calculating the Debt Service Coverage Ratio (DSCR) to assess the ability of the region to repay loans. The results showed that Bone Bolango Regency deserved a regional loan from the Central Government. This is because Bone Bolango fulfills 4 (four) loan requirements for the national economic recovery area.